Brief group‐based acceptance and commitment therapy for stroke survivors. (12th July 2018) - Majumdar, Sarah; Morris, Reg
Abstract : Objectives: To date, the efficacy of acceptance and commitment therapy (ACT) for stroke survivors has not been established. The aim of this study was to evaluate the efficacy of group‐based ACT for stroke survivors in comparison with treatment as usual (TAU) controls. Methods: Fifty‐three participants were randomly assigned either to group‐based ACT (ACTivate Your Life after Stroke) or to a TAU control group (60% male; mean age: 63 years). The ACT intervention consisted of four weekly 2‐hr didactic group sessions. Therapeutic effects were measured by examining changes in depression (primary outcome), anxiety, hope, health‐related quality of life, self‐rated health status, and mental well‐being. Measures were completed at pre‐treatment, post‐treatment, and 2‐month follow‐up. A mixed‐design repeated‐measures multivariate ANOVA was conducted to analyse the findings. Results: Analysis based on intention to treat found that compared to participants in the TAU control, group‐based ACT significantly reduced depression and increased self‐rated health status and hopefulness in stroke survivors, with medium effect sizes. Significantly more participants reached clinically significant change of depression in the ACT intervention in comparison with the control group. Conclusions: The results correspond with previous studies of group‐based ACT with other long‐term conditions. The findings from this current study suggest group‐based ACT may have promising utility and could offer a suitable low‐intensity psychological intervention for stroke survivors. However, further large‐scale research is required. Practitioner points: Acceptance and commitment therapy (ACT), delivered didactically to groups of stroke survivors, proved feasible and acceptable. ACT had benefits, relative to treatment as usual, for depression, health status, and hope. Several secondary outcome variables did not show dependable benefit for ACT: anxiety; health‐related quality of life; and mental well‐being. Results should be treated as preliminary as the sample size was small, blinding was not possible, concomitant treatments were not monitored, and there was no attention control condition. Despite these limitations, group‐based ACT merits further study as a potentially effective intervention.